2011
DOI: 10.4238/2011.november.4.8
|View full text |Cite
|
Sign up to set email alerts
|

AGPAT6 polymorphism and its association with milk traits of dairy goats

Abstract: ABSTRACT. As one of the eight members in the 1-acylglycerol-3-phosphate-O-acyltransferase (AGPATs) family, AGPAT6 is a crucial enzyme for the biosynthesis of glycerolipids and triacylglycerol in eukaryotes, as well as catalyzing the conversion from lysophosphatidic acid to phosphatidic acid. AGPAT6 can be considered as a candidate gene for regulating milk composition. DNA sequencing and PCR-RFLP methods were applied to detect genetic variation in the AGPAT6 gene in 549 Chinese dairy goats. Four polymorphisms (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Agpat6 À/À mice have a minimal phenotype: they showed reduced subdermal adipose tissue and had a defect in TAG production in mammary epithelium (gland) [26,27]. Further studies showed that AGPAT6 is the most abundant isoform in the mammary glands of lactating cows [28] and were substantiated by genome-wide association studies (GWAS) in Dutch dairy cattle [29], which has also been associated with milk traits in dairy goats [30]. The increased TAG in milk is attributed to increased expression of AGPAT6 which generates precursors for TAG synthesis.…”
Section: Human Agpat6 and Agpat10mentioning
confidence: 95%
“…Agpat6 À/À mice have a minimal phenotype: they showed reduced subdermal adipose tissue and had a defect in TAG production in mammary epithelium (gland) [26,27]. Further studies showed that AGPAT6 is the most abundant isoform in the mammary glands of lactating cows [28] and were substantiated by genome-wide association studies (GWAS) in Dutch dairy cattle [29], which has also been associated with milk traits in dairy goats [30]. The increased TAG in milk is attributed to increased expression of AGPAT6 which generates precursors for TAG synthesis.…”
Section: Human Agpat6 and Agpat10mentioning
confidence: 95%
“…Genes like the BDNF , FTO , or IGF1 impact upon food intake and thus nutrient and energy availability (Mullen et al, 2011 ; Zielke et al, 2011 , 2013 ; Waters et al, 2012 ). Other genes such as GHR , PRLR , or SPP1 affect growth, proliferation, and apoptosis of cells (Viitala et al, 2006 ; Khatib et al, 2007 ; Banos et al, 2008 ; Lu et al, 2011a ; Rahmatalla et al, 2011 ), whilst DGAT1 and AGPAT6 are involved directly in triglyceride synthesis (Winter et al, 2002 ; Bionaz and Loor, 2008a ; Strucken et al, 2010a ; He et al, 2011 ). Of further note are the casein genes which encode the major fraction of milk proteins (Velmala et al, 1995 ).…”
Section: Physiology Of a Dynamic Milk Productionmentioning
confidence: 99%
“…Additionally, other gene polymorphisms in goats are studied. For example, the AGPAT6 gene was found to significantly influence both the fat and protein contents and milk yield [ 53 ]. Additionally, the variability of the haplotypic sequences at the loci of the casein complex was studied [ 15 ].…”
Section: Resultsmentioning
confidence: 99%